The lion in West Africa is critically endangered. - Philipp Henschel (Public Library of Science (PLoS), 2014)
The African lion has declined to <35,000 individuals occupying 25% of its historic range. The situation is most critical for the geographically isolated populations in West Africa, where the species is considered regionally endangered. Elevating their conservation significance, recent molecular studies establish the genetic distinctiveness of West and Central African lions from other extant African populations. Interventions to save West African lions are urgently required. However formulating effective conservation strategies has been hampered by a lack of data on the species' current distribution, status, and potential management deficiencies of protected areas (PAs) harboring lions. Our study synthesized available expert opinion and field data to close this knowledge gap, and formulate recommendations for the conservation of West African lions. We undertook lion surveys in 13 large (>500 km²) PAs and compiled evidence of lion presence/absence for a further eight PAs. All PAs were situated within Lion Conservation Units, geographical units designated as priority lion areas by wildlife experts at a regional lion conservation workshop in 2005. Lions were confirmed in only 4 PAs, and our results suggest that only 406 (273-605) lions remain in West Africa, representing <250 mature individuals. Confirmed lion range is estimated at 49,000 km², or 1.1% of historical range in West Africa. PAs retaining lions were larger than PAs without lions and had significantly higher management budgets. We encourage revision of lion taxonomy, to recognize the genetic distinctiveness of West African lions and highlight their potentially unique conservation value. Further, we call for listing of the lion as critically endangered in West Africa, under criterion C2a(ii) for populations with <250 mature individuals. Finally, considering the relative poverty of lion range states in West Africa, we call for urgent mobilization of investment from the international community to assist range states to increase management effectiveness of PAs retaining lions.